A low temperature processed fused-ring electron transport material for efficient planar perovskite solar cells. Issue 47 (22nd November 2017) - Zhang, Mingyu; Zhu, Jingshuai; Liu, Kuan; Zheng, Guanhaojie; Zhao, Guanchao; Li, Liwei; Meng, Yuan; Guo, Ted; Zhou, Huanping; Zhan, Xiaowei
Abstract : A low temperature processed fused-ring electron acceptor IDIC is used as the electron transport layer in planar n–i–p perovskite solar cells, which exhibit higher efficiency and better stability than control devices based on TiO2 . Abstract : A fused-ring electron acceptor based on indacenodithiophene (IDIC) was used to replace TiO2 and work as an electron transport layer in planar n–i–p perovskite solar cells. IDIC improves perovskite crystallinity and film quality due to its hydrophobicity and incompatible wetting surface. IDIC facilitates electron extraction and transport due to its high mobility and suitable energy levels matched with the perovskite. IDIC reduces charge recombination in the devices due to trap passivation at the perovskite surface. The IDIC-based devices exhibit a champion power conversion efficiency of 19.1%, which is higher than that of TiO2 -based devices (17.4%). Moreover, the device stability is significantly improved by IDIC.